Simulation Analysis of Air Distribution in the Public Area of Single-Span Arch-Shaped Underground Station under the Centralized Air Return Mode - FENG Rao; LUO Yanping; LI Bijia; HU Zilin (Chengshi guidao jiaotong yanjiu)
［Objective］ Due to the relatively high floor height and the special structural form of arched top plates, the single-span arch-shaped underground station poses higher requirements for decoration. Therefore, it is necessary to study how to reduce the ventilation and air conditioning pipelines in the public areas of such underground stations on the premise of reasonable air distribution so as to provide more innovative space for decoration. ［Method］ In the case study of a single-span arch-shaped underground station in Shenzhen, ideas of adopting the centralized air return mode in the public area and the air supply duct design with smoke exhaust function are put forward. Under the conditions of the same cooling capacity and air supply temperature difference in the public area of the single-span arch-shaped underground station, the CFD (computational fluid dynamics) software is used to simulate and analyze the airflow temperature and speed distribution laws for the two air supply/return modes of single air supply/return and centralized air return. The impact of adjusting the position of the centralized air return inlet on the air distribution in the public area is also studied, and the non-uniformity coefficient is used for effect evaluation. ［Result & Conclusion］ Adopting the centralized air return mode in the public area of the underground station and designing the air supply duct with smoke exhaust function can effectively reduce about 50% of the hall air ducts, 40% of the cross-sectional area in the public area, and about 50% of the cross-sectional area of the platform air ducts. While adopting the centralized air return mode in the public area, the centralized air return inlets are separately arranged on the platform, together with the layout of air supply duct with smoke exhaust function, enabling the airflow temperature and speed distributions to reach a relatively excellent level. This centralized air return mode meets the comfort requirements of passengers, and is applicable to the air distribution in the public area of the single-span arched underground station.